On the Boness and Black-Scholes Models for Valuation of Call Options - Galai, Dan (Journal of Financial and Quantitative Analysis, 1978)
In this paper we confront two well-known models for pricing options. It shows how the two models, one derived in a discrete time framework by Boness, the other derived in a continuous time framework by Black and Scholes, can be made consistent. In doing so, we find the implicit, discrete period, discount factor for the call option. Several characteristics of the discount factor are analyzed and compared to the characteristics of the instantaneous expected rate of return on the call.